Towards a Process to Manage Usability Technical Debts - Costa, Alex Felipe Ferreira; Marques, Anna Beatriz Dos Santos; Santos, Ismayle Sousa; Andrade, Rossana Maria De Castro (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
Background: Technical Debt (TD) is a metaphor used to refer to the consequences of poor software development. TD can arise from immature source code to quality requirements that are not adequately addressed. Usability issues can be identified during a software project and, in turn, treated as TD. Studies conducted on real industry projects indicated that Usability Technical Debt (UTD) is frequent in software projects, is associated with relevant usability issues, and usually requires low effort for their payment. The systematic identification and management of UTD can contribute to how the project team acts in the face of usability problems, preventing these types of problems from reaching end-users and generating a positive impact on the use of the software. Aim: This research aims to provide a process that supports the early identification and management of UTD. Method: We adopted Design Science Research to create a process that comprises the identification, validation, rating, prioritization, estimation, and monitoring of UTD. Results: This paper presents the process with proposed activities, actors, and artifacts. Conclusions: We expect the process supports software development teams to deal with UTD systematically and contributes to improving the quality of the products developed.